Tecnica ELISA para detectar anticuerpos contra el virus de la rinotraqueitis infecciosa bovina - Barrera, M.=700 1 Peralta, E.L.; Noda, J.
(Es, En)
Ilus., 7 ref.
Keywords: HERPESVIRUS BOVINO; RINOTRAQUEITIS; TECNICAS ANALITICAS; DIAGNOSTICO; INMUNOLOGIA; CUBA; ELISA